Temperature smart control system - Lokman Mazidin, Muhamad Amirul Hafis; Yohya, Muhammad Faisal (2016)
Temperature control system is a device that detects, show and control the temperature of the laptop. This circuit can cool the heat generate by the laptop by operating a DC fan when the temperature in its vicinity increases above the trigger temperature. This project is to design a circuit that have LM35 as a sensor that can be attached with a microcontroller PIC16F877A. Other than that is to study the process and function of microcontroller and sensor that can be works together in one circuit. Moreover, to measured and read the temperature in a digital sign and overcome the problem. The simulation that is use in this project is Proteus. This project also is tested to breadboard to test the overall circuit. Microcontroller, PIC16F877A covert the temperature from analog signal to digital signal and send the data to the LCD to show the current and trigger temperature that has been set at the programming at the microcontroller PIC16F877A. If the temperature is higher than trigger temperature, the motor that act as cooling system will operate to cool down the laptop.